2021
DOI: 10.1101/2021.04.12.439463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative toxicogenomics of glyphosate and Roundup herbicides by mammalian stem cell-based genotoxicity assays and molecular profiling in Sprague-Dawley rats

Abstract: Background. Health effects from exposure to glyphosate-based herbicides is an intense matter of debate. Toxicity including genotoxicity of glyphosate alone has been repeatedly tested over the last 40 years. Contrastingly, few studies have conducted comparative investigations between glyphosate and its commercial herbicide formulations, such as Roundup. We thus performed the first in-depth comparative toxicogenomic evaluation of glyphosate and a typical European Union Roundup formulation by determining alterati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(105 reference statements)
2
2
0
Order By: Relevance
“…A similar effect of GLY in causing oxidative stress has been reported in the SH-SY5Y cell line [41] and rat liver [17]. Mesnage et al observed activated oxidative stress (reflected by Srxn1 and Blvrb) in mammalian stem cell-based ToxTracker system by glyphosatebased herbicides but not glyphosate itself [23], In our study, the expression level of Srxn1 and Blvrb (Fig. 3G and Additional file 2: Table S9) was improved after GLY exposure.…”
Section: Dysregulation Of Hepatocyte Signaling Induced By Glysupporting
confidence: 88%
See 3 more Smart Citations
“…A similar effect of GLY in causing oxidative stress has been reported in the SH-SY5Y cell line [41] and rat liver [17]. Mesnage et al observed activated oxidative stress (reflected by Srxn1 and Blvrb) in mammalian stem cell-based ToxTracker system by glyphosatebased herbicides but not glyphosate itself [23], In our study, the expression level of Srxn1 and Blvrb (Fig. 3G and Additional file 2: Table S9) was improved after GLY exposure.…”
Section: Dysregulation Of Hepatocyte Signaling Induced By Glysupporting
confidence: 88%
“…In addition, upregulation of genes involved in ribonucleoprotein complex assembly and ribonucleoprotein complex subunit organization in both Hep1 and Hep2 suggests potential DNA damage of GLY (Fig. 3E), which has been reported previously [23]. Overall, GLY may cause oxidative stress, abnormal lipid metabolism, inflammatory response, and DNA damage, suggesting GLY-induced dysregulation of hepatocytes.…”
Section: Dysregulation Of Hepatocyte Signaling Induced By Glysupporting
confidence: 78%
See 2 more Smart Citations